Integration of the Second Messenger c-di-GMP into the Chemotactic Signaling Pathway - Matthew H. Russell (American Society for Microbiology, 2013)
ABSTRACT Elevated intracellular levels of the bacterial second messenger c-di-GMP are known to suppress motility and promote sessility. Bacterial chemotaxis guides motile cells in gradients of attractants and repellents over broad concentration ranges, thus allowing bacteria to quickly adapt to changes in their surroundings. Here, we describe a chemotaxis receptor that enhances, as opposed to suppresses, motility in response to temporary increases in intracellular c-di-GMP. Azospirillum brasilense’s preferred metabolism is adapted to microaerophily, and these motile cells quickly navigate to zones of low oxygen concentration by aerotaxis. We observed that changes in oxygen concentration result in rapid changes in intracellular c-di-GMP levels. The aerotaxis and chemotaxis receptor, Tlp1, binds c-di-GMP via its C-terminal PilZ domain and promotes persistent motility by increasing swimming velocity and decreasing swimming reversal frequency, which helps A. brasilense reach low-oxygen zones. If c-di-GMP levels remain high for extended periods, A. brasilense forms nonmotile clumps or biofilms on abiotic surfaces. These results suggest that association of increased c-di-GMP levels with sessility is correct on a long-term scale, while in the short-term c-di-GMP may actually promote, as opposed to suppress, motility. Our data suggest that sensing c-di-GMP by Tlp1 functions similar to methylation-based adaptation. Numerous chemotaxis receptors contain C-terminal PilZ domains or other sensory domains, suggesting that intracellular c-di-GMP as well as additional stimuli can be used to modulate adaptation of bacterial chemotaxis receptors. IMPORTANCE To adapt and compete under changing conditions, bacteria must not only detect and respond to various environmental cues but also be able to remain sensitive to further changes in the environmental conditions. In bacterial chemotaxis, chemosensory sensitivity is typically brought about by changes in the methylation status of chemotaxis receptors capable of modulating the ability of motile cells to navigate in gradients of various physicochemical cues. Here, we show that the ubiquitous second messenger c-di-GMP functions to modulate chemosensory sensitivity of a bacterial chemotaxis receptor in the alphaproteobacterium Azospirillum brasilense. Binding of c-di-GMP to the chemotaxis receptor promotes motility under conditions of elevated intracellular c-di-GMP levels. Our results revealed that the role of c-di-GMP as a sessile signal is overly simplistic. We also show that adaptation by sensing an intracellular metabolic cue, via PilZ or other domains, is likely widespread among bacterial chemotaxis receptors.